Applications of VirScan to broad serological profiling of bat reservoirs for emerging zoonoses - Ruhs, Emily Cornelius; Chia, Wan Ni; Foo, Randy; Peel, Alison J.; Li, Yimei; Larman, H. Benjamin; Irving, Aaron T.; Wang, Linfa; Brook, Cara E. (Frontiers in Public Health, 2023)
We present the first full-application of Phage ImmunoPrecipitation Sequencing (PhIP-Seq) technology in a bat system, to describe the history of viral exposure in semi-captive populations of Pteropus alecto and Eonycteris spelaea fruit bats. Our paper provides the first record of antibody responses to several previously-unreported viruses in P. alecto serum, including alphaviruses, parvoviruses, and orthopoxviruses and offers a uniquely comprehensive window into associations between past viral exposures and bat health. As bats are largely assumed to be tolerant of most viruses, documentation of the subtle morbidity effects of infection is important. While prior studies have focused primarily on applications of PhIP-Seq to profiling antiviral immunity in humans and mice, here, we outline recommendations for its application to wildlife species. PhIP-Seq technology holds exciting potential as a tool to facilitate future surveillance efforts for potentially zoonotic viruses in wildlife reservoirs, including bats.